Level and determinants of contraceptive uptake among women attending facilities with abortion‐related complications in East and Southern Africa. (22nd October 2021) - Qureshi, Zahida; Jamner, Alanna; Filippi, Veronique; Gwako, George; Osoti, Alfred; Mehrtash, Hedieh; Baguiya, Adama; Bello, Folasade Adenike; Compaoré, Rachidatou; Gadama, Luis; Kim, Caron R.; Msusa, Ausbert Thoko; et al.
Abstract: Objective: To investigate the level and determinants of nonreceipt of contraception among women admitted to facilities with abortion‐related complications in East and Southern Africa. Methods: Cross‐sectional data from Kenya, Malawi, Mozambique, and Uganda collected as part of the World Health Organization (WHO) Multi‐Country Survey on Abortion‐related morbidity. Medical record review and the audio computer‐assisted self‐interviewing system were used to collect information on women's demographic and clinical characteristics and their experience of care. The percentage of women who did not receive a contraceptive was estimated and the methods of choice for different types of contraceptives were identified. Potential determinants of nonreceipt of contraception were grouped into three categories: sociodemographic, clinical, and service‐related characteristics. Generalized estimating equations were used to identify the determinants of nonreceipt of a contraceptive following a hierarchical approach. Results: A total of 1190 women with abortion‐related complications were included in the analysis, of which 33.9% ( n  = 403) did not receive a contraceptive. We found evidence that urban location of facility, no previous pregnancy, and not receiving contraceptive counselling were risk factors for nonreceipt of a contraceptive. Women from nonurban areas were less likely not to receive a contraceptive than those in urban areas (AOR 0.52; 95% CI, 0.30–0.91). Compared with women who had a previous pregnancy, women who had no previous pregnancy were 60% more likely to not receive a contraceptive (95% CI, 1.14–2.24). Women who did not receive contraceptive counselling were over four times more likely to not receive a contraceptive (AOR 4.01; 95% CI, 2.88–5.59). Conclusion: Many women leave postabortion care having not received contraceptive counselling and without a contraceptive method. There is a clear need to ensure all women receive high‐quality contraceptive information and counselling at the facility to increase contraceptive acceptance and informed decision‐making. Synopsis: Risk factors for nonreceipt of contraception among women attending health facilities with abortion‐related complications included attending a facility in an urban area, no previous pregnancy, and not receiving contraceptive counselling.